Application of Mobile Technology-Based Learning Analytics in Educational Assessment - Huang, Wei; Li, Xiping; Sun, Yijiao; Yang, Hao (International Journal of Interactive Mobile Technologies (iJIM), 2024)
With the rapid development of mobile technology, its application in the educational sector, particularly in learning analytics, has garnered increasing attention. The widespread adoption of modern mobile devices has introduced new opportunities for educational assessment. However, challenges remain in effectively utilizing these technologies for educational assessment. Current research predominantly focuses on data collection and analysis, yet the methods employed are limited in scope and application. This study aims to address these gaps by exploring data collection methods and teaching assessment approaches based on mobile technology. The objective is to contribute new perspectives and methodologies that modernize educational assessment. Through an in-depth analysis of the application of mobile technology in educational assessment, this study seeks to provide educators with scientifically grounded assessment tools and strategies, enabling more precise teaching management and personalized education.